Life, animated : a story of sidekicks, heroes, and autism - Suskind, Ron (2016)
The author describes how his autistic son, Owen, learned to cope with his handicap from a young age by memorizing the dialogue of Disney movies and having his family play the roles of the animated characters
Growing backward -- Bumping into walls -- In character -- Musical chairs -- The protekter of sidekicks -- A journey song -- Magic formulas -- Luck from unluck -- Blessings, undisguised -- The movie gods -- To do it on his own -- The animated life -- Sidekicks -- In the time since publication
Keywords: Suskind, Owen; Suskind, Ron -- Family; Disney, Walt, -- 1901-1966 -- Characters; Autistic children -- United States -- Biography; Parents of autistic children -- United States -- Biography; Autistic children -- Family relationships -- United States; Autistic children -- United States -- Language; Interpersonal communication -- United States; Animated films -- Psychological aspects; Autistic Disorder; Father-Child Relations; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; SOCIAL SCIENCE / People with Disabilities; Biographies; Biography; Biographies